2004
DOI: 10.4314/wsa.v27i1.5002
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cu(II) and Cr(VI) ions by chitosan: kinetics and equilibrium studies

Abstract: The ability of chitosan as an adsorbent for Cu (II) and Cr (VI) ions in aqueous solution was studied. The experiments were done as batch processes. Equilibrium studies were done on both cross-linked and non-cross-linked chitosan for both metals. Cr (VI) adsorption behaviour could be described using the Langmuir isotherm over the whole concentration range of 10 to 1000 mg·l -1 Cr. The maximum adsorption capacity for both types of chitosan was found to be 78 mg·g -1 for the non-cross-linked chitosan and 50 mg·g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
1
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 12 publications
12
178
1
11
Order By: Relevance
“…They reported that, the maximum adsorption of Cr (VI) occurred at pH 5 and decreased at lower and higher pH. Above pH 7 a plateau is observed (Schmuhl et al, 2001). Juang and Ju also in a same study regarding the effect of pH on Cu (II) ions adsorption on chitosan beads (ranged 3-9) reported that, removal efficiency increased first with increasing the pH and then reached a maximum at about pH 5-6, but, it decreased sharply with a further increase in equilibrium pH (Juang and Ju, 1997).…”
Section: Influence Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that, the maximum adsorption of Cr (VI) occurred at pH 5 and decreased at lower and higher pH. Above pH 7 a plateau is observed (Schmuhl et al, 2001). Juang and Ju also in a same study regarding the effect of pH on Cu (II) ions adsorption on chitosan beads (ranged 3-9) reported that, removal efficiency increased first with increasing the pH and then reached a maximum at about pH 5-6, but, it decreased sharply with a further increase in equilibrium pH (Juang and Ju, 1997).…”
Section: Influence Of Phmentioning
confidence: 99%
“…According to Tobin et al a variation of less than 0.5 units in the pH dose not affect the removal efficiency values (Marroun et al, 1998). Schmuhl et al (2001) studied the effect of the pH (varied between pH 2 and 11) on Cr (VI) sorption using chitosan beads. However, this study has been done on Cr (VI) ion removal from water and there is not similar report in case of polluted air.…”
Section: Influence Of Phmentioning
confidence: 99%
“…Therefore, it is necessary to remove Cr(VI) from wastewater before it is discharged to the natural water bodies. Various treatment technologies such as ion exchange, electrolytic removal, membrane filtration, reverse osmosis, chemical precipitation, adsorption, and solvent extraction have been reported for the removal of Cr(VI) from waste water [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Most of these technologies are associated with high operational and maintenance cost.…”
Section: Chromium Removal From Aqueous Solutionmentioning
confidence: 99%
“…From the literature, it is clear that chitosan is a plausible material to remove numerous metals, such as Cu(II), Pb(II), U(VI), Cr(III), Cr(VI), Ni(II), Cd(II), Zn(II), Co(II), Fe(II), Mn(II), Pt(IV), Ir(III), Pd(II), V(V), and V(IV) from heavy metal sources. 16 This kind of metal uptake stems from functional groups like hydroxyl, amino groups, and many hydrogen bonds, which function actively in the inter-and intramolecular structure among adsorbent, adsorbate, and biopolymer.…”
Section: Encapsulation Of Lead By Chitosanmentioning
confidence: 99%